(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The existence of extraterrestrial life has been a subject of human curiosity for centuries. From ancient myths to modern science fiction, aliens have captured the imagination of millions. Yet, despite the countless narratives and numerous scientific investigations, the question remains: are aliens merely a legend fabricated by human imagination, or is their existence a truth that awaits discovery? This paper explores the historical, cultural, and scientific dimensions of extraterrestrial life through the IMRAD structure (Introduction, Methods, Results, and Discussion), integrating evidence from astrophysics, exobiology, and sociology to determine the plausibility of alien life.